2012
DOI: 10.1292/jvms.11-0352
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study of Inflammatory Colorectal Polyps in Miniature Dachshunds

Abstract: ABSTRACT. Medical records of dogs with colorectal polyps were retrospectively reviewed, and clinical presentation of inflammatory colorectal polyps in miniature dachshunds was evaluated. Of 33 dogs found to have colorectal polyps, miniature dachshunds were markedly over-represented with 16 dogs (48%), of which 12 (75%) were found to have inflammatory polyps. Multiple polyps localized between the rectum and the descending colon was the most common finding in miniature dachshunds with inflammatory polyps. Twenty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
60
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 30 publications
2
60
1
Order By: Relevance
“…However, in some cases, immunosuppressive treatment results in a poor therapeutic response, ultimately requiring surgical removal. We previously reported that 1 of the 30 dogs included in a retrospective study developed adenoma during immunosuppressive therapy [12]. However, we later observed another dog developing adenoma secondary to ICRP that had been included as a dog with ICRPs that were well controlled with immunosuppressive therapy.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…However, in some cases, immunosuppressive treatment results in a poor therapeutic response, ultimately requiring surgical removal. We previously reported that 1 of the 30 dogs included in a retrospective study developed adenoma during immunosuppressive therapy [12]. However, we later observed another dog developing adenoma secondary to ICRP that had been included as a dog with ICRPs that were well controlled with immunosuppressive therapy.…”
mentioning
confidence: 86%
“…In summary, we described how adenomatous colorectal polyps developed secondary to ICRPs in 2 miniature dachshunds over a long period of time. In a previous retrospective study, we briefly reported that 1 of 30 miniature dachshunds with ICRP developed adenoma [12]. However, since a sufficient amount of time for adenoma development had elapsed after initial diagnosis in both cases, the possibility that other miniature dachshunds with well-controlled ICRPs would develop tumors in the future cannot be excluded.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…These polyps may be derived from neoplasms such as adenomatous polyps, or can be non-neoplastic lesions like inflammatory polyps [11,13,14]. We recently reported that inflammatory colorectal polyps are common in the Miniature Dachshund and typically form multiple diffuse polyps localized to the colon or rectum [8]. Immunosuppressive therapy with prednisolone and cyclosporine is suggested to be an effective treatment for the reduction of polyps and also amelioration of their associated clinical signs [8].…”
mentioning
confidence: 99%